Accessibility Considerations in the National Children's Study - Harniss, Mark; Magasi, Susan; Sabat, Dianne (Frontiers in Pediatrics, 2021)
In the National Children’s Study (NCS), assessments were proposed and developed that used a wide range of modes of administration (e.g., direct in-person interviews, telephone interviews, computer assisted interviews, self-administered questionnaires, real time and recall observations, and physical examinations). These modes of administration may pose accessibility challenges for some people with disabilities. Accessibility of measurement is important to consider because systematic exclusion of people with disabilities from research can lead to measurement bias and systematic error in derived scores. We describe our approach to analyzing the accessibility of measures in the NCS and describe the work of the Accessibility Domain Team. Finally, we describe a decision process for creating and using accessible health research measures.